2019
DOI: 10.3390/math7040374
|View full text |Cite
|
Sign up to set email alerts
|

New Numerical Aspects of Caputo-Fabrizio Fractional Derivative Operator

Abstract: In this paper, a new definition for the fractional order operator called the Caputo-Fabrizio (CF) fractional derivative operator without singular kernel has been numerically approximated using the two-point finite forward difference formula for the classical first-order derivative of the function f ( t ) appearing inside the integral sign of the definition of the CF operator. Thus, a numerical differentiation formula has been proposed in the present study. The obtained numerical approximation was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 40 publications
0
26
0
1
Order By: Relevance
“…Above all, there is not even a single field of study wherein fractional calculus has not been found beneficial to design and comprehend the complex behavior of deterministic and stochastic systems, for example see, [12][13][14][15][16][17][18] and most of the references cited therein. In short, many real world problems such as natural and biological ones are touched upon with the tools of fractional calculus making it a burning topic of today's era.…”
Section: Introductionmentioning
confidence: 99%
“…Above all, there is not even a single field of study wherein fractional calculus has not been found beneficial to design and comprehend the complex behavior of deterministic and stochastic systems, for example see, [12][13][14][15][16][17][18] and most of the references cited therein. In short, many real world problems such as natural and biological ones are touched upon with the tools of fractional calculus making it a burning topic of today's era.…”
Section: Introductionmentioning
confidence: 99%
“…This new fractional derivative is less affected by the past compared to the Caputo fractional derivative, which may exhibit slow stabilization [1,33]. The properties and numerical aspects of the CF derivative and their corresponding fractional integrals been studied in [2,6,8,11,18,30,38]. In this paper, we are interested in linear fractional-order neutral delay differential-algebraic equations described by the CF derivative.…”
Section: Introductionmentioning
confidence: 99%
“…The area of fractional calculus has currently become a burning area of study due to its numerous applications in almost every field of science, engineering and finance. Whether it be quantum mechanics, fluid dynamics, bio-medical, epidemiology, clinical biochemistry, chemical kinetics, statistical field theory, continuous random fields, electromagnetism, groundwater study, aerospace engineering, actuaries and many more as can be seen in recently conducted research studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and most of the references cited therein.…”
Section: Introductionmentioning
confidence: 99%